Effect of Treated Water with Aquatic Plant Residues on the Growth Parameters of Wheat (Triticum aestivum L.) in Two Different Soil Textures - Um Al-Banin Ahmed Akeb; Najla Jaber Al-Amiri , Najla Jaber Al-Amiri (University of Thi-Qar Journal of agricultural research, 2024)
A pot experiment was conducted using Triticum aestivum L. to study the effect of water treated with organic waste from aquatic plants (Azolla, Spirodela, and Lemna) on the growth parameters of wheat. Two types of soil were used: clay loam and sandy loam, within a factorial experiment involving three factors (water treatment type, filter type, and soil texture) with three replicates. Wheat seeds were planted, and the soil was fertilized with nitrogen, phosphorus, and potassium at a uniform level according to the recommended fertilization guidelines for wheat. The pots were irrigated according to the treatments, and after 60 days, the plants were harvested. Dry weight was recorded, and the nitrogen, phosphorus, potassium, sodium, and chloride content in the plant foliage was determined after digesting the plant samples. The results showed that clay loam soil irrigated with water filtered through Azolla had significantly better outcomes compared to sandy loam soil in all studied traits (dry weight, N, P, and K concentrations) and exhibited lower concentrations of sodium and chloride in the plants.